The Effectiveness of the Application of Batik Jumputan Skill to Improve Fine Motor Skill of Mild Intellectually Disabled Children in Special Schools throughout Semarang City - Martyana, Ratna; Diana, Diana (BELIA: Early Childhood Education Papers, 2018)
The aim of the study is to determine the effectiveness of the application of Batik Jumputan skill as an activity in improving the fine motor skill of mild intellectually disabled children in special schools throughout Semarang City. The research approach used is quantitative with the type of quasi-experimental research approach. The research design used is one group pre-test post-test. The subjects of this study are mild intellectually disabled children in special schools throughout Semarang City, in total 27 children. The data collection technique used is scale of fine motor skill with a number of 36 valid items that had previously been tested so that they could be used in the research, while the methods of data analysis are descriptive and hypothesis testing by using Paired Sample T Test. The results of the study showed that the level of fine motor skill of mild intellectually disabled children before being given the Batik Jumputan skill activities is included in the enough category with a percentage of 51.58% and after being given the Batik Jumputan skill activities included in the good category with a percentage of 48, 15%. Based on the results of the Paired Sample T Test obtained the value of < is (-12,724 <-2,056) with a significant value of 0,000, so Ho is rejected and Ha is accepted proving that there is significant difference in fine motor skill of mild intellectually disabled children after applied Batik Jumputan skills. The significant difference can be seen from the value of sig 2 tailed <0.05 is 0,000. It means that the use of Batik Jumputan in this study can improve the fine motor skill of mild intellectually disabled children.